Differences of Born Body Length, History of Infectious Diseases, and Development between Stunting and Non-Stunting Toddlers - Dewi Fitria Permatasari; Sri Sumarmi (Jurnal Berkala Epidemiologi, 2018)
ABSTRACTBackground: Stunting reflects the largely result of inadequate nutrition and attacks recurring infections in the first 1.000 days of life, that cause in develepmental obstacles. Purpose: This study was to analyze the differences born body length, history of infectious diseases, development between stunting, and non stunting children age 24-36 months. Methods: The type of this research was observational analytic with case control study. The sample size was 68 toddlers consist of 34 stunting childrens as case group and 34 non stunting children as control group in the catchment area of Jagir Public Helath Center in Surabaya. Sampling technique using simple random sampling. The observed variabls were born body length, history of infectious diseases, and child development. The data were collected using microtoise, questionnaire, and Denver Developmental Screening Test (DDST) sheets. Data were analyzed using chi square test. Results: This research showed significancy between stunting and non stunting children with difference of born body length (p = 0,01), history of infectious diseases (p = 0,01), and toddlers’ development (p = 0,01). Conclusion: There were difference variables of born body length, history of infectious diseases, and development between stunting and non stunting children age 24-36 months.